2011
DOI: 10.1523/jneurosci.6401-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Triggers Exocytosis from Two Types of Organelles in a Single Astrocyte

Abstract: Astrocytes release a variety of signaling molecules including glutamate, D-serine, and ATP in a regulated manner. Although the functions of these molecules, from regulating synaptic transmission to controlling specific behavior, are well documented, the identity of their cellular compartment(s) is still unclear. Here we set out to study vesicular exocytosis and glutamate release in mouse hippocampal astrocytes. We found that small vesicles and lysosomes coexisted in the same freshly isolated or cultured astroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
130
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(142 citation statements)
references
References 62 publications
(120 reference statements)
11
130
0
Order By: Relevance
“…11,12,20,44 We show that astrocyte cell membrane injury causes a greater [Ca 2+ ] c increase, triggering more robust lysosome exocytosis. Receptor stimulation causes a sustained and low rate of exocytosis where lysosomes release a part of their luminal content and none of their membrane proteins (Figures 2 and 6).…”
Section: Discussionmentioning
confidence: 68%
“…11,12,20,44 We show that astrocyte cell membrane injury causes a greater [Ca 2+ ] c increase, triggering more robust lysosome exocytosis. Receptor stimulation causes a sustained and low rate of exocytosis where lysosomes release a part of their luminal content and none of their membrane proteins (Figures 2 and 6).…”
Section: Discussionmentioning
confidence: 68%
“…However, quinacrine also binds ATP with a high affinity (23,24) and is commonly used to visualize ATP-containing vesicles, including lysosomes (6,7,25,26). We provide new evi- dence that quinacrine intensity correlates with lysosomal ATP levels rather than lysosomal acidic pH.…”
Section: Discussionmentioning
confidence: 88%
“…Therefore, in these cells, lysosomes may be the major secretory vesicles that release ATP. Previously, others have reported that ATP accumulated in lysosomes of astrocytes (6,26) and microglia (7) and lysosomal ATP release via lysosomal exocytosis is implicated in ischemic insult (6) and cell migration (7). However, the molecular mechanisms underlying ATP accumulation in these cells remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Upon stimulation, lysosomes translocate from the perinuclear and cytosolic regions to the plasma membrane along the microtubules (33)(34)(35)(36). After docking, lysosomes fuse directly with the plasma membrane to release the lysosomal content into the extracellular space ( Fig.…”
Section: Lysosomal Lipid Storage Disordersmentioning
confidence: 99%